Iminosugar C‐Glycosides Work as Pharmacological Chaperones of NAGLU, a Glycosidase Involved in MPS IIIB Rare Disease. Issue 44 (2nd July 2021) - Zhu, Sha; Jagadeesh, Yerri; Tran, Anh Tuan; Imaeda, Shuki; Boraston, Alisdair; Alonzi, Dominic S.; Poveda, Ana; Zhang, Yongmin; Désiré, Jérôme; Charollais‐Thoenig, Julie; Demotz, Stéphane; Kato, Atsushi; et al.
Abstract: Mucopolysaccharidosis type IIIB is a devastating neurological disease caused by a lack of the lysosomal enzyme, α‐ N ‐acetylglucosaminidase (NAGLU), leading to a toxic accumulation of heparan sulfate. Herein we explored a pharmacological chaperone approach to enhance the residual activity of NAGLU in patient fibroblasts. Capitalizing on the three‐dimensional structures of two modest homoiminosugar‐based NAGLU inhibitors in complex with bacterial homolog of NAGLU, CpGH89, we have synthesized a library of 17 iminosugar C ‐glycosides mimicking N ‐acetyl‐D‐glucosamine and bearing various pseudo‐anomeric substituents of both α‐ and β‐configuration. Elaboration of the aglycon moiety results in low micromolar selective inhibitors of human recombinant NAGLU, but surprisingly it is the non‐functionalized and wrongly configured β‐homoiminosugar that was proved to act as the most promising pharmacological chaperone, promoting a 2.4 fold activity enhancement of mutant NAGLU at its optimal concentration. Abstract : Capitalizing on the X‐ray structure of two NAGLU‐homoiminosugar complexes, the synthesis and evaluation as glycosidase inhibitors of a library of rationally designed iminosugar C ‐glycosides led to the discovery of several selective NAGLU inhibitors and allowed the identification of a pharmacological chaperone candidate to treat mucopolysaccharidosis type IIIB, a rare and devastating disease.